Penggunaan Buku Tulis Indah Garis Tiga untuk Meningkatkan Keterampilan Menulis Siswa Kelas 2 SD Negeri Bongkilemba Kecamatan Tompobulu Kabupaten Gowa - Sarmila Sarmila; Yuddin Pasiri; Aco Karumpa (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Sarmila, 2023. This research is based on the results of interviews conducted by researchers with grade 2 teachers at Bongkilemba State Elementary School, obtained information that in teaching writing the teacher has not maximized and applied appropriate learning media so that students experience difficulties in developing ideas and ideas, and in the end students only copy what already exists. For writing beginners, the teacher should guide students to write, starting from the stage of generating ideas and ideas, developing ideas and ideas to the writing stage as a whole. The teacher also has never used the three-line beautiful notebook media to help students generate ideas and ideas. Based on the results of observations at the pre-research stage, information was obtained that in learning Indonesian, especially writing, the teacher only used lecture, question and answer and assignment methods. In addition, teachers also do not use media in learning activities. It can be concluded that students find it difficult in generating and developing ideas and ideas. In fact, the emergence of ideas and ideas is one of the processes that must be done before writing. Teachers have not used the media especially for learning to write